Business cycles and monetary policy asymmetry: An investigation using Markov-switching models - TAN, S; HABIBULLAH, M (ELSEVIER SCIENCE BV, 2007)
This study assesses empirically the effects of monetary policy on four ASEAN economies in different states. The idea of asymmetry is being examined by using the relatively popular technique of non-linear modeling-Hamilton's Markov regime-switching model. The findings confirmed the existence of two-regimes in all economies under study. Additionally, the null hypothesis of symmetry had been rejected in the case of the four economies and to a great extent, monetary policy was confirmed to have had larger effects during recessions. These findings, thus, may imply the important role that credit market imperfections have on a firm's investment behavior, which in turn suggests that the financial accelerator is a relevant mechanism underscoring the observed asymmetry. (c) 2007 Elsevier B.V. All rights reserved.